Mitochondrial Bioenergetics at the Onset of Drug Resistance in Hematological Malignancies: An Overview - Barbato, Alessandro; Scandura, Grazia; Puglisi, Fabrizio; Cambria, Daniela; La Spina, Enrico; Palumbo, Giuseppe Alberto; Lazzarino, Giacomo; Tibullo, Daniele; Di Raimondo, Francesco; Giallongo, Cesarina; Romano, Alessandra (Frontiers in Oncology, 2020)
The combined derangements in mitochondria network, function and dynamics can affect metabolism and ATP production, redox homeostasis and apoptosis triggering, contributing to cancer development in many different complex ways. In hematological malignancies, there is a strong relationship between cellular metabolism, mitochondrial bioenergetics, interconnections with supportive microenvironment and drug resistance. Lymphoma and chronic lymphocytic leukemia cells, e.g., adapt to intrinsic oxidative stress by increasing mitochondrial biogenesis. In other hematological disorders such as myeloma, on the contrary, bioenergetics changes, associated to increased mitochondrial fitness, derive from the adaptive response to drug-induced stress. In the bone marrow niche, a reverse Warburg effect has been recently described, consisting in metabolic changes occurring in stromal cells in the attempt to metabolically support adjacent cancer cells. Moreover, a physiological dynamic, based on mitochondria transfer, between tumor cells and their supporting stromal microenvironment has been described to sustain oxidative stress associated to proteostasis maintenance in multiple myeloma and leukemia. Increased mitochondrial biogenesis of tumor cells associated to acquisition of new mitochondria transferred by mesenchymal stromal cells results in augmented ATP production through increased oxidative phosphorylation (OX-PHOS), higher drug resistance, and resurgence after treatment. Accordingly, targeting mitochondrial biogenesis, electron transfer, mitochondrial DNA replication, or mitochondrial fatty acid transport increases therapy efficacy. In this review, we summarize selected examples of the mitochondrial derangements in hematological malignancies, which provide metabolic adaptation and apoptosis resistance, also supported by the crosstalk with tumor microenvironment. This field promises a rational design to improve target-therapy including the metabolic phenotype.